WORKING WITH THE APARTHEID ARCHIVE: OR, OF WITNESS AND TESTIMONY - Laubscher, Leswin (PINS-Psychology in Society, 2025)
Working with the apartheid archive demands a spectral scholarship – an engagement with the dead and the past, and the unknown of a future-to-be. This “hauntology” poses challenges unlike those of a traditional, evidentiary ontology and epistemology. Indeed, to the extent that it is an ethical metaphysics, as proposed by Emmanuel Levinas, that motivates all knowing, including that of the self and psyche, the manner of the researcher’s response is in the order of witnessing and testimony. As particular mode of response, the witness who testifies sees his or her task less in terms of generating totalising thematic knowledge, than in tracing the limits of knowledge in the experience of the other.